Antibacterial activity of alkyl gallates is a combination of direct targeting of FtsZ and permeabilization of bacterial membranes - Król, Ewa; de Sousa Borges, Anabela; da Silva, Isabel; Polaquini, Carlos R.; Regasini, Luis O.; Ferreira, Henrique; Scheffers, Dirk-Jan (Frontiers in Microbiology, 2015)
Alkyl gallates are compounds with reported antibacterial activity. One of the modes of action is binding of the alkyl gallates to the bacterial membrane and interference with membrane integrity. However, alkyl gallates also cause cell elongation and disruption of cell division in the important plant pathogen Xanthomonas citri subsp. citri, suggesting that cell division proteins may be targeted by alkyl gallates. Here, we use Bacillus subtilis and purified B. subtilis FtsZ to demonstrate that FtsZ is a direct target of alkyl gallates. Alkyl gallates disrupt the FtsZ-ring in vivo, and cause cell elongation. In vitro, alkyl gallates bind with high affinity to FtsZ, causing it to cluster and lose its capacity to polymerize. The activities of a homologous series of alkyl gallates with alkyl side chain lengths ranging from five to eight carbons (C5-C8) were compared and heptyl gallate was found to be the most potent FtsZ inhibitor. Next to the direct effect on FtsZ, alkyl gallates also target B. subtilis membrane integrity – however the observed anti-FtsZ activity is not a secondary effect of the disruption of membrane integrity. We propose that both modes of action, membrane disruption and anti-FtsZ activity, contribute to the antibacterial activity of the alkyl gallates. We propose that heptyl gallate is a promising hit for the further development of antibacterials that specifically target FtsZ.